COMPARISON OF IPS LEARNING RESULTS USING MONOPOLY MEDIA AND POWER POINT MEDIA - Yuli Mulyawati; Resyi A Ghani (UNIVERSITAS PAKUAN, 2019)
This research using comparative methods. The purpose of this research is to compare the learning outcomes of learning IPS by using Media Monopoly and Media Powerpoint . This research was conducted at SDN Katulampa 1 in Bogor City Class VA, and VB in August odd semester 2019/2020. The analysis technique used is the analysis prerequisite test which includes a normality test, a homogeneity test, then a research hypothesis is carried out using the t test. The results empirically n shows that there perbendingan learning outcomes in Media Monopoly seen in the average score - average N-Gain 8 5 de ngan mastery learning outcomes 92 %, while the average score - average N-Gain on Media Power Point that is equal to 75 with the thoroughness of the results belaja r 86 %. ) . And the results of testing the hypothesis states that H o rejected and H a accepted because t arithmetic (1.67469) t table (1.67469). Based on the above results, it can be concluded that there is a comparison of the results of learning by using Media Monopoly and Media Power Point , and Media efektif is Media Monopoly.